2018
DOI: 10.1002/joc.5444
|View full text |Cite
|
Sign up to set email alerts
|

Teleconnections between ENSO and rainfall and drought in Puerto Rico

Abstract: An analytical study was conducted to assess the long‐term influence, role, and impacts of El Niño‐Southern Oscillation (ENSO) on Puerto Rico's precipitation patterns and significant moisture deficits (droughts). Detection and attribution was addressed by evaluating local rainfall measures and ENSO‐related data to (1) detect ENSO signals and patterns, (2) quantify the magnitude of any impacts, and (3) determine if ENSO may be an important factor for local prediction of future droughts. Data were evaluated at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…2a, f) and are indicating the presence of a La-Niña state in the winter preceding a dry ERS. The relationship is weak given the weak ENSO-ERS correlations, similarly to that found in some previous studies (Malmgren et al 1998;Jury et al 2007;Torres-Valcárcel 2018). A simple way to evaluate the relative roles of the NAO and ENSO in the ERS is by using Kendall's Tau (τ), a non-parametric rank correlation coefficient, which takes into consideration issues such as outliers, and the non-gaussian distribution of rainfall.…”
Section: Relationship Between Ers and Enso/naomentioning
confidence: 58%
See 3 more Smart Citations
“…2a, f) and are indicating the presence of a La-Niña state in the winter preceding a dry ERS. The relationship is weak given the weak ENSO-ERS correlations, similarly to that found in some previous studies (Malmgren et al 1998;Jury et al 2007;Torres-Valcárcel 2018). A simple way to evaluate the relative roles of the NAO and ENSO in the ERS is by using Kendall's Tau (τ), a non-parametric rank correlation coefficient, which takes into consideration issues such as outliers, and the non-gaussian distribution of rainfall.…”
Section: Relationship Between Ers and Enso/naomentioning
confidence: 58%
“…Several studies have attributed the interannual variability of the Caribbean to two large-scale climate modes of variability: The El Niño-Southern Oscillation (ENSO) and the North Atlantic Oscillation (NAO). In the Caribbean, ENSO was found to affect both the ERS (Giannini et al 2000(Giannini et al , 2001cChen and Taylor 2002;Taylor et al 2002;Gouirand et al 2012), during boreal spring, when ENSO events end, and the LRS during boreal fall when events are mature (Giannini et al 2000(Giannini et al , 2001cTaylor et al 2002;Spence et al 2004;Wang et al 2006;Rodriguez-Vera et al 2019)., Other studies found no significant correlation between ENSO and rainfall in the Central and Eastern Caribbean (Chen and Taylor 2002;Malmgren et al 1998;Torres-Valcárcel, 2018;Hernández Ayala 2019) and showed instead that in those regions, rainfall is highly correlated with the NAO (Malmgren et al 1998;Giannini et al 2001c;Gouirand et al 2012;Mote et al 2017). The NAO, which exhibits peak variability in the boreal winter months, affects the Hadley Circulation and corresponding NASH (Wang 2001), SSTs in the tropical North Atlantic region (TNA) (Bjerknes 1964;Kushnir 1994;Seager et al 2000;Hurrell et al 2003;Kushnir et al 2006) and consequently rainfall, during the Caribbean ERS (George and Saunders 2001;Giannini et al 2001c;Rodriguez-Vera et al 2019).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Puerto Rico's climate is regulated by interactions between large scale systems such as the North Atlantic Oscillation (NAO), Saharan Dust advection and African easterly waves, and local island effects (Comarazamy & González, 2011; Comarazamy et al., 2013; Hosannah et al., 2017; Jury et al., 2009). While the National Weather Service (NWS, 2016) indicates that ENSO also impacts the island's climate; approximately 13% more precipitation occurs during El Niño years in the dry season and 14% more precipitation occurs during La Niña years in the wet season, recent studies by Torres‐Valcárcel (2018) and Hernández‐Ayala (2019) found no significant correlation between ENSO and the island's rainfall despite the ENSO anomaly accounting for nearly 30% of rainfall variability over the Caribbean region. Generally, a warm ENSO (El Niño) event will result in negative sea surface temperature anomalies in the tropical North Atlantic and will lead to negative rainfall anomalies in the Caribbean region during the summer months.…”
Section: Introductionmentioning
confidence: 99%